Preliminary Studies on the Use of Sawdust and Peanut Shell Powder as Adsorbents for Phosphorus Removal from Water - Marian Asantewah Nkansah; Moses Donkoh; Osei Akoto; James Hawkins Ephraim (Ital Publication, 2019)
Phosphorus is one of the key nutrients that contribute to eutrophication and excess algal growth in rivers, lakes, and other surface water bodies. Such algal blooms affect the lives of aquatic organisms, especially fish, and block sunlight from reaching bottom dwelling plants, thus inhibiting photosynthesis and stunting growth. In this study, sawdust and peanut shell powder were explored as adsorbents for the removal of phosphorus from aqueous solutions. A series of batch experiments were conducted to determine the effects of adsorbent dosage, initial phosphorus concentration, and contact time on the rate of phosphorus removal. The results showed that 78% and 39% of phosphorus were removed by sawdust and peanut shell powder, respectively, at adsorbate concentrations of 10 mg/l (total P) for a period of 180 min at an adsorbent dosage of 0.4 g. It was also found that the highest phosphorus removal occurred at an adsorbent mass of 0.4 g of sawdust and 0.6 g of peanut shell powder. Adsorption data was fitted to the linearised forms of the Freundlich and Langmuir isotherm models to determine the water-adsorbent partitioning coefficient. Sawdust proved to be a better adsorbent than peanut shell powder.